SAT0202 Efficacy and safety of sarilumab monotherapy versus adalimumab monotherapy in patients with active rheumatoid arthritis in the phase 3 monarch study, including subpopulations. (15th June 2017) - Burmester, GR; Lin, Y; Mangan, EK; Hoogstraten, H van; Kimura, T; Vargas, JI; Lee, EB
Abstract : Background: Efficacy and safety of sarilumab + csDMARDs in RA patients have been demonstrated. Objectives: To compare sarilumab monotherapy with adalimumab monotherapy in the ITT population of adults with active RA from MONARCH (NCT02332590 ) and across predefined subgroups. Methods: Adults (N=369) intolerant of, inappropriate for, or inadequate responders (IR) to MTX (per investigator judgment) received SC sarilumab 200 mg q2w or adalimumab 40 mg q2w monotherapy. The primary endpoint was change from baseline in DAS28-ESR at wk 24. Consistency of treatment response (sarilumab vs adalimumab) for this endpoint was assessed in prespecified subpopulations. Results: At wk 24, sarilumab was superior to adalimumab in change from baseline (BL) in DAS28-ESR (-3.3 vs -2.2; P <0.0001). Sarilumab-treated patients achieved significantly higher rates of ACR20 response (71.7% vs 58.4%; P =0.0074) and greater improvement in HAQ-DI (-0.6 vs -0.4; P =0.0037) and CDAI (-28.9 vs -25.2; nominal P =0.0013) vs adalimumab-treated patients. Extent of treatment effect with sarilumab vs adalimumab in change from baseline in DAS28-ESR at wk 24 was generally consistent ( P >0.05) across subgroups; significant treatment-by-subgroup interactions were observed for body mass index ( P =0.047) and baseline CRP ( P =0.006) (Figure). The magnitude of treatment effect for DAS28-ESR was greater in patients with lower BMI and higher baseline CRP. Treatment effect was generally similar for other efficacy endpoints assessed, including ACR20, HAQ-DI, and CDAI. Clinical and functional responses in RF+/ACPA+, RF+/ACPA-, RF-/ACPA+, and RF-/ACPA- patients were similar to overall study results. Incidence of AEs was similar in both groups, including incidences of infections and serious infections. The most common AEs were neutropenia and injection site erythema (sarilumab) and headache and worsening of RA (adalimumab). Conclusions: Sarilumab monotherapy demonstrated superiority to adalimumab monotherapy in the ITT population in change from baseline in DAS28-ESR. The extent of treatment effect with sarilumab vs adalimumab was generally consistent across subpopulations. Overall incidences of AEs and serious AEs and rates of infection and serious infection were similar between groups. Acknowledgements: This study was sponsored by Sanofi Genzyme and Regeneron Pharmaceuticals, Inc. Medical writing support was provided by MedThink SciCom and funded by Sanofi Genzyme and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: G. Burmester Grant/research support from: AbbVie, Bristol-Myers Squibb, MedImmune, Merck, Pfizer, Roche, and UCB, Consultant for: AbbVie, Bristol-Myers Squibb, MedImmune, Merck, Pfizer, Roche, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Merck, Pfizer, Roche, and UCB, Y. Lin Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, E. Mangan Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, H. van Hoogstraten Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, T. Kimura Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. Vargas Grant/research support from: Roche, Bristol-Myers Squibb, and Pfizer, Speakers bureau: Bristol-Myers Squibb, E. Lee Consultant for: Pfizer